EFFECTIVENESS OF THE USE OF THE K-MOB MOBILE ATTENDANCE APPLICATION AMONG TEACHERS AT SMAN 8 GARUT - Hermawan, Yusuf (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Since 2020, Sekolah Menengah Atas Negeri (SMAN) 8 Garut has implemented an online teacher attendance system through a mobile attendance application known as K-Mob. However, in practice, over the past three years, the K-Mob application has not been effective. This study aims to assess the effectiveness of using the K-Mob application for teacher attendance at SMAN 8 Garut. The research employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out by interpreting data, tables, and images to draw conclusions. This study utilizes Tangkilisan's (2005) effectiveness theory as the analytical framework, which outlines that effectiveness comprises four aspects: target achievement, adaptability, job satisfaction, and responsibility. The results of the study concluded that the use of the K-Mob application at SMAN 8 Garut has not been effective.